2009
DOI: 10.1007/s12223-009-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus strains: in vitro and in vivo studies

Abstract: Three Lactobacillus strains (LOCK 0900, LOCK 0908, LOCK 0919) out of twenty-four isolates were selected according to their antagonistic activity against pathogenic bacteria, resistance to low pH and milieu of bile salts. Intragastric administration of a mixture of these strains to Balb/c mice affected cytokine T(H)1-T(H)2 balance toward nonallergic T(H)1 response. Spleen cells, isolated from lactobacilli-treated mice and re-stimulated in vitro with the mixture of heat-inactivated tested strains, produced signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 18 publications
(11 reference statements)
1
47
0
3
Order By: Relevance
“…In vitro tests conducted on probiotic strains revealed the strains' resistance to low pH and bile salts (Cukrowska et al, 2009) and showed antagonistic activity against pathogenic bacteria. Moreover, the probiotic strains also synthesize bacteriocins resistant to proteolytic enzymes, e.g., biosurfactans with described antimicrobial function.…”
Section: Characterisation and Preparation Of Probiotic Strainsmentioning
confidence: 99%
“…In vitro tests conducted on probiotic strains revealed the strains' resistance to low pH and bile salts (Cukrowska et al, 2009) and showed antagonistic activity against pathogenic bacteria. Moreover, the probiotic strains also synthesize bacteriocins resistant to proteolytic enzymes, e.g., biosurfactans with described antimicrobial function.…”
Section: Characterisation and Preparation Of Probiotic Strainsmentioning
confidence: 99%
“…30 These selected strains showed properties required for probiotic bacteria, e.g., resistance to gastric acids and bile salts and inhibitory activities against bacterial pathogens. 30 Moreover, the mixture of these strains (Lmix) showed synergistic effects in the induction of anti-allergic Th1-type cytokines and regulatory cytokine TGF-b in human whole blood cell cultures compared with the levels induced by each single strain alone.…”
Section: Introductionmentioning
confidence: 99%
“…30 These selected strains showed properties required for probiotic bacteria, e.g., resistance to gastric acids and bile salts and inhibitory activities against bacterial pathogens. 30 Moreover, the mixture of these strains (Lmix) showed synergistic effects in the induction of anti-allergic Th1-type cytokines and regulatory cytokine TGF-b in human whole blood cell cultures compared with the levels induced by each single strain alone. 31 Our pilot study showed that the supplementation of children presenting the first symptoms of allergy (atopic dermatitis) with the Lmix reduced serum levels of IgE and IL-5 and diminished the severity of the disease (Cukrowska, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…37 The bacteria were found in the intracellular spaces of lymphocytes and macrophages in Peyer's patches. 36 Cukrowska et al reported that lactobacillus cells administered intragastrically did not translocate through the intestinal barrier into blood, liver and spleen, but were found alive in a mesenteric lymph node, although the localization of the bacteria in a mesenteric lymph node was not shown.…”
Section: Discussionmentioning
confidence: 99%